PENGEMBANGAN MEDIA PEMBELAJARAN E-BOOKLET MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Indah Resti Ayuni Suri; Bambang Sri Anggoro; Deva Putri Yuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students have difficulty understanding concepts, so they are afraid to learn mathematics. The purpose of this study is to produce E-Booklets as a learning media product and testing the worthiness of E-Booklets as learning media to improve understanding the concepts of seventh grade students of SMP Negeri 1 Labuhan Ratu, East Lampung. This Research and Development (R&D) used the model development based on Borg and Gal theory. In this study, only 7 steps were carried out, there are initial information collection, planning, initial product development, initial trial, product revision, field trial, product revision. The results obtained from the validation results carried out by 5 validators indicate that the Integer Numbers E-Booklet learning media meets the Very Eligible criteria. The score obtained from the results of media expert validation is 72% (Validator I); (Validator II) and 75% (Validator III), the results of material expert validation are 87% (Validator I); 87% (Validator II) and 74% (Validator III). Thus, the E-Booklet as a learning media to improve understanding of the concepts of class VII students is seen from the N-Gain value of 0.59 with moderate criteria and the results of student responses with a score of 89% with Very Eligible Criteria Keywords: Learning Media 1,E-Booklet 2,Concept Understanding 3